Trends, burden, and risk factors of stomach cancer in China, 1990 - 2021 - Kevin Lu; Xiangxiang Jiang; Gang Lv; Jing Yuan (The Lancet Regional Health. Western Pacific)
Background: Stomach cancer is the third leading cause of cancer-related deaths in China. While the incidence and mortality rates have shown a declining trend, attributed to changes in lifestyle and ongoing prevention efforts, it remains a significant health concern due to the country's large population and low survival rates. This study aimed to investigate the burden, trends, and risk factors of stomach cancer in China over the past three decades. Understanding these aspects is crucial for informing public health strategies and interventions, which can ultimately contribute to improved outcomes and resource allocation in the fight against stomach cancer. Methods: Data for this study were sourced from the Global Burden of Disease (GBD) study 2021, a thorough initiative that assesses the impact of 371 diseases and 88 risk factors across 204 countries and territories. The Global Health Data Exchange (GHDx) query tool, an online platform for health data offered by the Institute for Health Metrics and Evaluation, was utilized to collect annual age-standardized incidence rate (ASIR), age-standardized mortality rate (ASMR), and age-standardized disability-adjusted life years (ASDALYs) related to stomach cancer. In the GBD study, risk factors are organized into four levels, with Level 1 representing the broadest categories and Level 4 comprising the most specific factors. Due to data limitations, this study focused on gathering data related to the Level 3 risk factor groups associated with stomach cancer. Findings: In 2021, the ASIR, ASMR, and ASDALYs for stomach cancer in China were 29.05, 21.51, and 627.98 per 100,000, with average annual percent change (AAPC) of -0.40, -0.53, and -0.58, respectively, compared to 1990. The AAPC reductions for incidence, mortality, and DALYs decreased with increasing age for individuals over 45, with the 45-49 age group exhibiting the highest reductions in AAPCs. Additionally, the ASIR, ASMR, and ASDALYs among males were higher than those among females from 1990 to 2021. The AAPCs for ASIR, ASMR, and ASDALYs were -0.50, -0.60, and -0.64 in females, while in males, they were -0.34, -0.50, and -0.54, indicating an increased sex disparity. The main risk factors contributing to stomach cancer mortality were smoking and high sodium consumption, accounting for 14.36% and 8.30%, respectively. Interpretation: This study highlighted the ongoing challenge of stomach cancer in China, emphasizing its significant health burden despite declining incidence and mortality rates. The findings indicated notable disparities in both age and sex, with younger individuals and females experiencing higher reductions in AAPCs of stomach cancer. These insights underscored the importance of developing targeted public health strategies that can address specific demographics, particularly those high-risk groups. Additionally, recognizing smoking and high sodium intake as significant risk factors highlighted the necessity for comprehensive prevention strategies, such as educational campaigns that encourage healthier lifestyle choices. Improving screening and early detection efforts was vital for enhancing survival rates and overall outcomes. By addressing these factors, healthcare resources could be allocated more effectively, ultimately helping to lessen the impact of stomach cancer in China.